2016
DOI: 10.1039/c6ee00526h
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing charge separation on high symmetry SrTiO3exposed with anisotropic facets for photocatalytic water splitting

Abstract: Spatial charge separation achieved on the anisotropic facets of high symmetry SrTiO3 nanocrystals for highly efficient photocatalytic overall water splitting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
294
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(314 citation statements)
references
References 54 publications
9
294
0
Order By: Relevance
“…[32,33] Recently, the Domen group reported a breakthrough achievement for overall water splitting based on particulate photocatalyst sheets. [24,31,[34][35][36][37][38][39][40] The solar energy conversion efficiency has been improved significantly during the past few years. The powders of the photocatalysts were embedded into an Au layer, which functioned as the electron mediator between the two components of the Z-scheme system.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…[32,33] Recently, the Domen group reported a breakthrough achievement for overall water splitting based on particulate photocatalyst sheets. [24,31,[34][35][36][37][38][39][40] The solar energy conversion efficiency has been improved significantly during the past few years. The powders of the photocatalysts were embedded into an Au layer, which functioned as the electron mediator between the two components of the Z-scheme system.…”
Section: Photocatalytic Water Splittingmentioning
confidence: 99%
“…[1] Forp hotocatalysis,t he photogenerated electrons (e À )and holes (h + )need to be efficiently separated and transferred to the surface reactive sites of the catalysts to participate in the reductive and oxidative reactions,r espectively. [5] Therefore,i ti sm eaningful to prepare as ingle-crystal photocatalyst with special surface structures containing spatially separated reductive and oxidative catalytic sites to reduce the recombination of photoexcited e À and h + and consequently improve the photocatalytic activity. [5] Therefore,i ti sm eaningful to prepare as ingle-crystal photocatalyst with special surface structures containing spatially separated reductive and oxidative catalytic sites to reduce the recombination of photoexcited e À and h + and consequently improve the photocatalytic activity.…”
mentioning
confidence: 99%
“…[9][10][11][12][13][14][15] It has been reported that selective deposition of suitable dual-cocatalysts (oxidation cocatalysts and reduction cocatalysts) on corresponding sites of semiconductor-based crystals (e.g., BiVO 4 , TiO 2 , SrTiO 3 , PbTiO 3 ) resulted in a remarkable enhanced photocatalytic performance due to the spatial separation of the photogenerated charges between different facets and the synergetic effect of dual-cocatalysts deposited onto the needed facets. 13,[16][17][18][19][20][21][22] Our recent research works revealed that the square-like WO 3 nanoplates with Pt loaded mainly on dominant facets shows higher photocatalytic activity than that with Pt loaded on the edged facets due to light-induced charge separation between different facets of square-like WO 3. 23 However, the activity difference is not very big owe to that platinum particles were not effective oxidation reaction promoters for promoting O 2 evolution on the dominant (002) facets of square-like WO 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Such a decreased electron-hole recombination might be ascribed to selective deposition of a suitable dual-cocatalysts onto the needed facets of square-like WO 3 leading accelerated transfer of the photogenerated electrons and holes from the surfaces of WO 3. It has been reported that the deposition of suitable dualcocatalysts on the needed facets of semiconductor-based crystals (e.g., BiVO 4 , TiO 2 ) resulted in a remarkable synergetic effect in the photocatalytic performance, which could be attributed to the spatial separation of the photogenerated charges between facets. 13,16,22 Our recent research works reveal that light-induced preferential ow of photogenerated holes and electrons to the dominant (002) facets and edged facets of square-like WO 3 , on which oxidation and reduction occurs, respectively. 23 Here we proposed the reaction mechanism of visible-light-driven O 2 evolution over the square-like WO 3 loaded with Pt and PbO x dual cocatalysts as depicted in Fig.…”
mentioning
confidence: 99%